Rent-a-girlfriend. Volume 12 - Miyajima, Reiji (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2022)
"Kazuya's second date with the school-uniform-clad Sumi at the aquarium continues. Sure, things got off to a bit of a hectic start, but now that they're at the live aquatic show, they can finally relax and enjoy things right? Poor Kazuya's been absolutely distraught trying to think up a way to help Mizuhara, and maybe a chaotic distraction is just what he needs. A little fresh air can really clear the head, or was it fresh water?"--Amazon.